2023
DOI: 10.7554/elife.86469
|View full text |Cite
|
Sign up to set email alerts
|

A class-specific effect of dysmyelination on the excitability of hippocampal interneurons

Delphine Pinatel,
Edouard Pearlstein,
Giulia Bonetto
et al.

Abstract: The role of myelination for axonal conduction is well-established in projection neurons but little is known about its significance in GABAergic interneurons. Myelination is discontinuous along interneuron axons and the mechanisms controlling myelin patterning and segregation of ion channels at the nodes of Ranvier have not been elucidated. Protein 4.1B is implicated in the organization of the nodes of Ranvier as a linker between paranodal and juxtaparanodal membrane proteins to the spectrin cytoskeleton. In th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 69 publications
(122 reference statements)
0
2
0
Order By: Relevance
“…Another compelling function of PV interneuron myelin sheaths is the clustering of mitochondria and thus the fine tuning of metabolic requirements during axonal activation [ 67 ]. Interestingly, other GABAergic neuron subtypes such as a fraction of somatostatin (SST)-expressing interneurons and, to a much lesser extent, vasoactive intestinal peptide (VIP)-expressing interneurons have myelin sheaths with layer-specific arrangements [ 63 , 68 , 69 ]. However, the functional and structural significance of this myelination, sometimes limited to a single internode per axon, remains largely unexplored, pointing to avenues for further investigation.…”
Section: Myelination Heterogeneity In the Cortexmentioning
confidence: 99%
See 1 more Smart Citation
“…Another compelling function of PV interneuron myelin sheaths is the clustering of mitochondria and thus the fine tuning of metabolic requirements during axonal activation [ 67 ]. Interestingly, other GABAergic neuron subtypes such as a fraction of somatostatin (SST)-expressing interneurons and, to a much lesser extent, vasoactive intestinal peptide (VIP)-expressing interneurons have myelin sheaths with layer-specific arrangements [ 63 , 68 , 69 ]. However, the functional and structural significance of this myelination, sometimes limited to a single internode per axon, remains largely unexplored, pointing to avenues for further investigation.…”
Section: Myelination Heterogeneity In the Cortexmentioning
confidence: 99%
“…However, the functional and structural significance of this myelination, sometimes limited to a single internode per axon, remains largely unexplored, pointing to avenues for further investigation. Nevertheless, it has recently been reported that a myelin loss in SST interneurons in the hippocampus can be associated with a reduction in their firing frequency [ 69 ]. Finally, comparisons between seven different GABAergic and glutamatergic neurons show significant variations in their myelination patterns, with PV interneurons and thalamocortical axons exhibiting higher myelination probabilities [ 63 ].…”
Section: Myelination Heterogeneity In the Cortexmentioning
confidence: 99%